Study of weak vibrating signal detection based on chaotic oscillator in MEMS resonant beam sensor. (January 2015) - Shi, Huichao; Fan, Shangchun; Xing, Weiwei; Sun, Jinhao
Abstract: In this paper, the application of weak signal detection based on chaotic oscillator is studied in a MEMS resonant beam sensor. Chaotic oscillator can detect weak signal which is submerged in the background of large noise. According to the frequency and phase characteristic of the output vibrating signal, reference current signal with fixed frequency difference and same phase to the output signal is set. Frequency and phase of the signal are fixed by detection resistor which works as a multiplier. By calculating the maximum Lyapunov exponent, detection threshold is obtained, and motion change of detection system is monitored. The results of numerical simulation and experiment show that this method can effectively detect the weak resonant signal and find the resonant frequency accurately by setting the threshold of the chaotic oscillator, and it is immune to the noise. Highlights: Chaotic oscillator is applied in detection of weak resonant signal of MEMS sensor. Detection resistor is used to fix frequency and phase of detected signal. By maximum Lyapunov exponent, we get detection threshold and monitor chaotic motion.